Correlates of sexual health service use amongst unmarried young adults in Kathmandu, Nepal - Jayasinghe, Joshua; Ulrich, Connie M.; Shrestha, Anju; Sherpa Awasthi, Mamata; Chittams, Jesse; Rice, Bridgette M.; Shrestha, Prakash; Teitelman, Anne M. (Frontiers in Reproductive Health, 2025)
BackgroundIn Nepal, sexual relationships outside of the traditional arranged marital system are increasingly common. Despite the availability of modern sexual health care, research on how to effectively deliver sexual health services to unmarried young adults in Nepal is limited.ObjectiveThis study examined key theoretical correlates between Andersen's Behavioral Model of Health Service Use and actual sexual health service use among unmarried young adults (aged 18 to 25) in Kathmandu, Nepal.MethodsUnmarried young adults between 18 and 25 were recruited from colleges and universities in the Kathmandu area. A total of 110 women and 93 men completed the survey (n = 203). Using a cross-sectional correlational design, the analysis involved descriptive statistics, bivariate analysis, and logistic regression.Findings and conclusionsApproximately 37% of participants reported engaging in sexual intercourse, with 55.7% reporting condom use during most recent intercourse. Less than half (39.1%) were aware of available sexual health services, and less than one-third (26.6%) were aware of Human Papillomavirus (HPV). Over a third of participants (40.9%) reported experiencing unwanted sexual contact, and 5.9% had a history of forced sexual intercourse. The actual reported sexual health service use within the past 12 months was 13.9%. Logistic regression analyses showed higher perceived youth friendliness of the health system (OR: 1.19; CI: 1.01–1.39; p < .05), sexual attraction to the same or both sexes (OR: 2.91; 95%; CI: 1.54–5.50; p < .01), higher perceived sexual risk (OR: 1.33; 95%; CI: 1.11–1.59; p < .01), as well as prior health awareness and behaviors (e.g., cigarette consumption, dating app use), were statistically significant correlates of sexual health service use. These findings indicate a need for further research to understand the experiences of Nepalese young adults with sexual healthcare and essential elements of youth-friendly health systems.